Macula-predominant retinopathy associated with biallelic variants in RDH12. (1st November 2020) - Ba-Abbad, Rola; Arno, Gavin; Robson, Anthony G.; Bouras, Konstantinos; Georgiou, Michalis; Wright, Genevieve; Webster, Andrew R.; Michaelides, Michel
ABSTRACT: Purpose: To describe the clinical, electrophysiological, and molecular features of an unusual macula-predominant retinopathy in two unrelated probands with biallelic variants in RDH12 . Methods: Retrospective case series Results: A 29-year-old female presented with visual loss since the age of 14 years. Retinal examination revealed symmetric outer retinal atrophy in the posterior pole with peripapillary sparing. Fundus autofluorescence (AF) showed patchy loss of AF in the posterior pole, with hyper-autofluorescent borders. Optical coherence tomography (OCT) showed loss of the macular outer retinal layers. Pattern electroretinography (PERG) showed macular dysfunction and full-field ERG indicated mild loss of photoreceptor function. Next-generation sequencing (NGS) identified two variants in RDH12 : p.(Arg234His) and c.448 + 1 G > A in trans . The second patient was a 10-year-old male with bilateral macular changes and visual loss. Retinal examination showed bilateral macular cloverleaf-like outer retinal changes, with relative foveal sparing. Fundus AF showed bilateral macular hypo-autofluorescent patches with a border of increased signal and preserved foveal AF. OCT showed attenuation of the perifoveal outer retinal layers in the regions of reduced AF signal. PERG showed macular dysfunction, but the full-field ERG was normal. NGS and whole-genome sequencing identified two variants in RDH12 : p.(Arg234His) and p.(Cys245_Leu247deI) in trans . Conclusions: Disease-causing variants in RDH12 are typically associated with early-onset severe retinal dystrophy with significant macular involvement. Hypomorphic alleles of this gene cause relatively mild retinopathy with predominant macular involvement. This phenotype demonstrates the vulnerability of the macular photoreceptors to certain perturbations of RDH12 .